Pemberdayaan Diet Omega-3 sebagai Antihiperkolesterolemia di Masa Pandemi Covid-19 pada Mahasiswa Kedokteran UPN Veteran Jakarta - Kristina Simanjuntak; Arman Yurisaldi Saleh; Boenga Nur Cita (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Hypercholeleolemia or dyslipidemia triggers free radical formation and atherosclerosis associated with heart disease, the highest cause of death in Indonesia. Hypercholesterolemia is caused by overeating, obesity, diabetes mellitus (DM) tipe-2, cardiovascular disease, hypertension, stress cancer, genetics, alcohol, the elderly, lack of activity, vegetables and fruits. Atherosclerosis triggers the formation of Angiotensin-Converting Enzyme 2 (ACE-2) which is a receptor for the entry of coronavirus 2 (SARS-CoV-2) in the lungs, which needs to be anticipated during the Covid 19 pandemic. Receptor-bound viruses can disrupt the respiratory system and death. Dietary omega 3 from fish or supplements serves as an anti-hypercholesterolemia, anti-inflammatory, anti-hyperglycemic, and anti-thrombotic. The purpose is the empowerment of omega-3 diet as anti-hypercholesterolemia in UPNVJ Medical students during the Covid 19 pandemic. The method used, determining body mass index (BMI) and assessing diet and physical activity using a food frequency questionnaire. As a result, the provision of omega-3 dietary knowledge in 147 FK UPN students who attended through multimedia PPT online, obtained a body mass index (BMI) above normal 35 respondents, with overweight 60% and obesity 40%. Results from the frequency food questionnaire showed a high-carbohydrate diet of 98%, fish consumption of 2.63%, omega 3 supplements of 10.52%, aerobic physical activity of 17.14%, of sleep and play mobile phones of 100%, of vegetables 5.71% and of the fruit of 17.14%. The formation of hypercholesterolemia occurs in a diet high in carbohydrates, saturated lipids, low in omega 3 diet, vegetables, and physical activity. The empowerment of an omega 3 diet can inhibit hypercholesterolemia which is good for health.